Indicadores de desempenho para a logística reversa de embalagens em geral para Palmas/TO - Camargo, Roseanne Veloso de (Universidade Federal do Tocantins, 2022)
The 8th article of the Brazilian National Solid Waste Policy (BNSWP) identifies reverse logistics as a management instrument, together with selective collection and other instruments related to the implementation of the shared responsibility for solid waste management. However, the execution of reverse logistics and selective collection is shared by several representatives of the public and private sectors, especially in Palmas municipality, location of the object of this study, where there is no public selective collection in the door-to-door model. It is up to the Municipal Government to propose objectives and goals to carry out the reverse logistics of various types of solid waste, including packaging in general (mentioned in the first paragraph of the 33rd article of the BNSWP), terminology used in the Sectoral Agreement, which covers a large part of the recyclable materials. The verification of compliance with these goals is done through performance indicators, and this work starts from a criticism by the authors of the existing indicators, which are currently in use by the management of the municipality of Palmas/TO. Thus, proposing a set of seven new performance indicators for local municipal managers, in order to quantify and qualify the fulfillment of what was proposed in the sectorial agreement for the reverse logistics of packaging in general was the objective of this research. The methodology used was the documentary research, carried out from a sample of Integrated Solid Waste Management Municipal Plans, with the largest municipalities in Tocantins State and that have these Plans being pre-selected; and the similar population size, with municipalities around 300,000 inhabitants being also selected (considering between 200,000 and 400,000 inhabitants). 71 Integrated Solid Waste Management Municipal Plans were then compiled in an embracing sample with all regions of Brazil, and their contents were read in search of indicators ranging from selective collection to reverse logistics of packaging in general and several auxiliary worksheets were filled in, whose results were filtered based on selected criteria according to the theoretical framework raised. The results show the indicators raised in tables, and the application of the filtering steps of the results from the selected criteria, until the presentation of a results table with seven indicators that met the pre-defined criteria. These indicators range from evaluating the existence of a law regulating reverse logistics to the percentage of establishments that participate in reverse logistics in the municipality. Finally, it was concluded that it is possible to propose performance indicators that interact with the existing and current Sectoral Agreements, and the Reverse Logistics, instruments of the Brazilian National Solid Waste Policy.